Assessment of omeprazole and famotidine effects on the pharmacokinetics of tacrolimus in patients following kidney transplant–randomized controlled trial - Miedziaszczyk, Miłosz; Karczewski, Marek; Grabowski, Tomasz; Wolc, Anna; Idasiak-Piechocka, Ilona (Frontiers in Pharmacology, 2024)
Tacrolimus is metabolized in the liver with the participation of the CYP3A4 and CYP3A5 enzymes. Proton pump inhibitors are used in kidney transplant patients to prevent duodenal and gastric ulcer disease due to glucocorticoids. Omeprazole, unlike famotidine, is a substrate and inhibitor of the enzymes CYP2C19, CYP3A4, CYP3A5. The aim of this study was to compare the impact of omeprazole and famotidine on the pharmacokinetics of tacrolimus.A randomized, non-blinded study involving 22 stabilized adult kidney transplant patients was conducted. Patients received the standard triple immunosuppression regimen and omeprazole 20 mg (n=10) or famotidine 20 mg (n=12). The study material consisted of blood samples in which tacrolimus concentrations were determined using the Chemiluminescent Microparticle Immuno Assay method.A single administration of omeprazole increased tacrolimus concentrations at 2h (day 2) = 11.90 ± 1.59 ng/mL vs 2h (day 1 -no omeprazole administration) = 9.40 ± 0.79 ng/mL (p=0.0443). AUC0-6 amounted to 63.07 ± 19.46 ng × h/mL (day 2) vs 54.23 ± 10.48 ng × h/mL (day 1), (p=0.0295). AUC2-6 amounted to 44.32 ± 11.51 ng × h/mL (day 2) vs 38.68 ± 7.70 ng × h/mL (day 1), (p=0.0130). Conversely, no significant changes in values of pharmacokinetic parameters were observed for famotidine.Omeprazole significantly increases blood exposure of tacrolimus. The administration of famotidine instead of omeprazole seems safer for patients following kidney transplantation.ClinicalTrials.gov Identifier: NCT05061303.